Utility of CT in the diagnosis of prosthetic valve abnormalities. Issue 11 (21st August 2020) - Velangi, Pratik S.; Kalra, Rajat; Markowitz, Jeremy; Nijjar, Prabhjot S.
Abstract: Background: Patients with prosthetic heart valves (PHV) are at an increased risk of endocarditis and dysfunction. Knowledge about the etiology of dysfunction and extent of endocarditis can have distinct treatment implications. Echocardiography has limitations due to PHV‐related artifacts. We hypothesized that computed tomography (CT) will have incremental value over echocardiography for evaluation of PHV abnormalities with surgical findings as the reference standard. Methods: Consecutive patients with PHV that had a reoperation for valve replacement, had a contrast chest CT and echocardiogram within 1 year of the reoperation, between 2010 and 2018 at a single academic center formed the study cohort. CTs and echocardiograms were assessed for potential etiologies of dysfunction (valve degeneration, pannus and thrombus); and for extent of endocarditis (vegetation, abscess, and pseudoaneurysm). Results: Seventy‐three patients (65.8% male, mean age 62.1 ± 16.5 years) formed the study cohort. The indication for reoperation was PHV dysfunction in 51 and PHV endocarditis in 22. Compared to echocardiography, CT diagnosed the etiology of PHV dysfunction in 17 (33.3%) more patients (9 valve degeneration, 8 pannus). In the PHV endocarditis cohort, CT failed to detect one vegetation and one abscess, whereas echocardiography failed to detect 1 abscess. In combination, CT and echocardiography demonstrated all the vegetations and abscesses. Conclusion: CT may provide superior characterization in comparison to echocardiography for the identification of the cause of prosthetic valve dysfunction, and complementary information to echocardiography for the evaluation of prosthetic valve endocarditis.